Odvračanje kot iluzija ali uporaben koncept obrambe majhnih držav? Študija primera osamosvojitve Slovenije - Furlan, Branimir (Dileme, 2026)
The article discusses the problems of implementing the concept of deterrence against attacks on small countries. Based on a case study of the Slovenian independence process, the author points out some of the challenges of successful deterrence in practice and questions the usefulness of insisting on the concept of deterrence in national security and defence strategies in circumstances where its success is unlikely. In response to this question, he highlights the Slovenian experience, particularly from the war for Slovenia, where the strategy of denial succeeded to deter the aggressor from continuing the war. The lessons learned can be useful for small countries facing military threats in the modern era.
Keywords: denial; deterrence; odvračanje; onemogočanje; osamosvojitev Slovenije; Slovenian independence; Vojaška strategija; Vojna v Sloveniji (1991)